SQUiD: ultra-secure storage and analysis of genetic data for the advancement of precision medicine - Jacob Blindenbach; Jiayi Kang; Seungwan Hong; Caline Karam; Thomas Lehner; Gamze Gürsoy (Genome Biology)
Abstract Cloud computing allows storing the ever-growing genotype-phenotype datasets crucial for precision medicine. Due to the sensitive nature of this data and varied laws and regulations, additional security measures are needed to ensure data privacy. We develop SQUiD, a secure queryable database for storing and analyzing genotype-phenotype data. SQUiD allows storage and secure querying of data in a low-security, low-cost public cloud using homomorphic encryption in a multi-client setting. We demonstrate SQUiD’s practical usability and scalability using synthetic and UK Biobank data.